(untitled) (International Educators Conference, 2025)
The article analyzes the philosophical views of the ancient Greek philosopher Plato, in particular, the essence of ideas and their role in the process of human cognition. Plato’s theory of knowledge, the idea of anamnesis (remembering), as well as the moral and social significance of ideas are scientifically examined.